Fragment optimized chalcone derivatives targeting OmpA protein as a therapeutic approach against multidrug resistant Acinetobacter baumannii - Muhammad Naveed; Amina Abid; Tariq Aziz; Ayesha Saleem; Arooj Arshad; Khushbakht Javed; Hafiz Muzzammel Rehman; Ghulam Nabi; Mitub Al-harbi; Abdullah F. Alasmari (Scientific Reports)
Abstract Acinetobacter baumannii is a notorious pathogen associated with life-threatening infections, with its outer membrane protein A (OmpA) being a key contributor to its pathogenicity by targeting epithelial cell apoptosis. The study presents an in silico analysis of chalcone derivatives as potential therapeutic agents against the outer membrane protein A (OmpA) of Acinetobacter baumannii. We performed molecular docking to evaluate the binding interactions, revealing that isobavachalcone exhibited the highest binding affinity. Further fragment optimization (FOI) of isobavachalcone improved its binding energy. Additionally, ADMET (absorption, distribution, metabolism, excretion, and toxicity) analysis was conducted to assess the pharmacokinetic properties of the compounds. Antigenicity and allergenicity of the protein show that this protein is virulent and antigenic. Moreover, molecular docking was performed and the result shows that isobavachalcone showed the highest binding energy at -6.7 kcal/mol. Furthermore, for a more potent compound, fragment optimization was performed and led to a new lead compound fragment optimized isobavachalcone (FOI) which shows increased binding energy −6 kcal/mol. ADMET and toxicity analysis was performed of both the compounds isobavachalcone and FOI which revealed favorable pharmacokinetic profiles for both compounds, but toxicity analysis showed discrepancies, with the isobavachalcone exhibiting toxicity but FOI compound showing no detectable toxicity. This underscores the importance of structure optimization in drug development. Overall, chalcone derivatives show promise as antibacterial agents against A. baumannii, with computational analyses aiding in compound selection and optimization. While both isobavachalcone and its FOI showed favorable pharmacokinetics, in vivo and in vitro validation is needed to confirm their therapeutic potential.